DEVELOPING INFORMATION COMPETENCE IN FUTURE PRIMARY SCHOOL TEACHERS THROUGH VIRTUAL TECHNOLOGIES: IMPLEMENTATION OF A SYSTEM-BASED APPROACH (International Congress on Economics, Management and Business Studies, 2026)
This paper examines the role of virtual technologies in developing information competence among future primary school teachers and proposes a system-based approach for integrating digital tools into teacher education. The study emphasizes the importance of digital transformation in education and highlights how virtual learning environments enhance pedagogical preparation, self-directed learning, and professional adaptability.The research findings suggest that structured implementation of virtual technologies significantly improves students’ ability to access, analyze, and apply information in educational contexts. The proposed model includes diagnostic, motivational, theoretical-practical, and monitoring stages aimed at systematically developing information competence in teacher training programs.
Keywords: information competence, virtual technologies, digital education, primary education, teacher training, ICT integration.